Semi-Small Compressible Modules and Semi-Small Retractable Modules - Hashim Al Hakeem, Mohammed Baqer; Nuhad S. Al-Mothafar; Maryam Haghjooyan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Let be a commutative ring with 1 and be left unitary . In this paper we introduced and studied concept of semi-small compressible module (a is said to be semi-small compressible module if can be embedded in every nonzero semi-small submodule of . Equivalently, is semi-small compressible module if there exists a monomorphism , , is said to be semi-small retractable module if , for every non-zero semi-small sub module in . Equivalently, is semi-small retractable if there exists a homomorphism whenever . In this paper we introduce and study the concept of semi-small compressible and semi-small retractable s as a generalization of compressible and retractable respectively and give some of their advantages characterizations and examples.